Numerical study of wake characteristics in a horizontal-axis hydrokinetic turbine - Silva, Paulo Augusto Strobel Freitas e (2016)
Over the years most studies on wake characteristics have been devoted to wind turbines, while few works are related to hydrokinetic turbines. Among studies applied to rivers, depth and width are important parameters for a suitable design. In this work, a numerical study of the wake in a horizontal-axis hydrokinetic turbine is performed, where the main objective is an investigation on the wake structure, which can be a constraining factor in rivers. The present paper uses the Reynolds Averaged Navier Stokes (RANS) flow simulation technique, in which the Shear-Stress Transport (SST) turbulent model is considered, in order to simulate a free hydrokinetic runner in a typical river flow. The NREL-PHASE VI wind turbine was used to validate the numerical approach. Simulations for a 3-bladed axial hydrokinetic turbine with 10 m diameter were carried out, depicting the expanded helical behavior of the wake. The axial velocity, in this case, is fully recovered at 12 diameters downstream in the wake. The results are compared with others available in the literature and also a study of the turbulence kinetic energy and mean axial velocity is presented so as to assess the influence of proximity of river surface from rotor in the wake geometry. Hence, even for a single turbine facility it is still necessary to consider the propagation of the wake over the spatial domain.